Analisis pengaruh kompensasi, budaya kerja dan gaya kepemimpinan transformasional terhadap motivasi intrinsik serta dampaknya pada kinerja karyawan PT. Sentra Strategis Indonesia (SSI) Jakarta Selatan - Gunawan, Heri; Efendi, Suryono (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of compensation, work culture and transformational leadership style on intrinsic motivation and their impact on employee performance at PT. Indonesian Strategic Center (SSI) South Jakarta. This study uses a survey method by distributing questionnaires to employees of PT. The Indonesian Strategic Center (SSI) South Jakarta as the respondent. The results showed that compensation and transformative leadership style directly had a positive and significant effect on intrinsic motivation. Intrinsic motivation directly has a positive and significant effect on employee performance. Compensation and work culture have a positive and significant effect on employee performance. Work culture has a direct positive and insignificant effect on intrinsic motivation. Transformational leadership style has a positive and insignificant effect on employee performance. Compensation, work culture and transformational leadership style indirectly through intrinsic motivation have a positive and significant effect on the performance of PT. Indonesian Strategic Center (SSI) South Jakarta.